Three-Dimensional Map of Isoprognostic Zones in Glottic Cancer Treated by Transoral Laser Microsurgery as a Unimodal Treatment Strategy - Piazza, Cesare; Filauro, Marta; Paderno, Alberto; Marchi, Filippo; Perotti, Pietro; Morello, Riccardo; Taboni, Stefano; Parrinello, Giampiero; Incandela, Fabiola; Iandelli, Andrea; Missale, Francesco; Peretti, Giorgio (Frontiers in Oncology, 2018)
Introduction: The UICC-AJCC TNM staging system for glottic squamous cell carcinoma (SCC) includes different types of lesions defined by the involvement of specific subsites in each T category. Our study aims to identify different subcategories according to tumor local extension and determine oncologic outcomes after treatment by transoral laser microsurgery (TLM) alone. Methods: We retrospectively evaluated 410 patients affected by previously untreated pT1-pT3 glottic SCC treated by TLM alone from January 2005 to December 2015 at the Departments of Otorhinolaryngology – Head and Neck Surgery, Universities of Genoa and Brescia, Italy. All patients had at least 2 years of follow-up. Clinical, radiological, surgical, and histopathological data were reviewed and tumors divided into 6 subcategories: I, pT1a not involving the anterior commissure (AC); II, pT1b involving the AC; III, pT2 extending superficially to the supraglottis or the subglottis; IV, pT2 infiltrating the vocal muscle; V, pT3 involving the anterior paraglottic space; VI, pT2 or pT3 with vertical extension across the AC with/without involvement of the pre-epiglottic space. Recurrence-free survival (RFS), local control with laser alone (LCL), and organ preservation (OP) were defined as the primary oncologic outcomes. Results: The 2, 5, and 10-year RFS for the entire series were 85.7%, 80.3%, and 73.8%, LCL rates 93.8%, 92.1%, and 89.6%, and OP rates 96.8%, 95.9%, and 93.5%, respectively. However, when comparing the rates of RFS, LCL, and OP for each subcategory, important differences emerged. In particular, subcategories V and VI showed a significantly increased risk of local recurrence (hazard ratio [HR]=9.2 and 13.3, respectively). These subcategories also had a significantly reduced probability to achieve LCL (HR=73.6 and 93.5, respectively), and OP (HR=6.4 and 8.1, respectively). Conclusion: The present classification in subcategories allows introducing the concept of a 3D map of isoprognostic zones in glottic SCC treated by TLM alone as a useful tool in its management by a multidisciplinary tumor board.